RESPON KONSUMEN TERHADAP PEMBERITAAN DITEMUKANNYA FORMALIN PADA PRODUK PANGAN OLAHAN (CONSUMERS RESPONSE TOWARDS NEWS OF THE FORMALIN USAGE ON PROCESSED FOOD PRODUCT) - WIDODO -; SITI YUSI RUDIMAH (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2008)
The negative news about small or home industries food production that was published bymass media has a large impact on it’s marketing. This research was conducted to explain theattitude and consumers behaviour change toward food that was issued of formalin usage topreserving. This descriptive research was conducted with survey to 42 households in urban,50 households in sub urban, and 26 householeds in rural territory. The results showed thatnegative news of formalin usage to food preserving decreased the consumer’s believe towardsthe food safety, the tendency to consume, rose the consumer buying selectivity and decreasedthe consumer buying intensity. The consumer’s believe towards the food safety, the tendencyto consume, the consumer buying intensity will increased after the publishing of promotifnews such as public figure consuming that food, but the buying selectivity still arose. Thepositive news of no formalin usage on food that was published increased again theconsumer’s believe towards the food safety, the tendency to consume, the consumer buyingselectivity and the consumer buying intencity but not recovered